Immediacy factors as solutions to email satisfactory communication among South-East Nigerian academic staff: structural equation modeling and preliminary findings - Anumudu, Chinedu Eugenia; Megat Al Imran Yasin,; Akmar Hayati Ahmad Ghazali,; Syed Agil Shekh Alsagoff, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Notwithstanding the evidence of utilizing email among Nigerian academic staff as shown in the previous studies, a recentstudy demonstrated that they witnessed dissatisfactory communication via email as textbased communication medium. Therefore, the aim of our study was to evaluate if immediacy factors might influence their email satisfactory communication since these factors have been ascertained in the past studies as predictors to satisfactory communications in other asynchronous virtual communications. The respondents’ email satisfactory communication levels were further examined in the study for finding if they also contributed to their email dissatisfactory communication. Hence, a quantitative research method was conducted because the study required both descriptive and inferential studies for the aim of inferring the outcomes to the targeted population. Consequently, our key findings showed that more than half of the respondents’ email satisfactory communication level was not a high one. Additionally, our findings showed that the three immediacy factors which comprised prompt feedback, approachability and similar personality had direct effects on email satisfactory communication. However, similar personality factor contributed most to email satisfactory communication. Therefore, we recommend that they should consider these three immediacy factors, especially the similar personality if they aim to achieve email satisfactory communication. Our findings further explicitly contributed knowledge to asynchronous computer-mediated media satisfactory communication.